1995
DOI: 10.1159/000126989
|View full text |Cite
|
Sign up to set email alerts
|

Increased Number of Corticotropin-Releasing Hormone Expressing Neurons in the Hypothalamic Paraventricular Nucleus of Patients with Multiple Sclerosis

Abstract: Observations in experimental allergic encephalomyelitis (EAE), a model for multiple sclerosis (MS), have indicated that a low activity of the hypothalamo-pituitary-adrenal (HPA) system is accompanied by a high susceptibility for EAE in rat strains and that elevated corticosteroid levels are necessary for spontaneous recovery from EAE. The HPA axis activity is regulated by both corticotropin-releasing hormone (CRH) and arginine vasopressin (AVP). Both types of neurons are localized in the paraventricular nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 17 publications
0
22
0
4
Order By: Relevance
“…Considering that two phenotypic CRF neurons occur in the PVN (one non-AVP-producing and the other AVP-coproducing) [32] and that the signal-driving ACTH secretion depends on the nature, intensity, and duration of the stressor [2], it is tempting to speculate that, in contrast to AA in EAE, the non-AVP-producing neuron is the predominant driving neuron, at least in the later stages of the disease (after 11 days). This notion is reinforced by results in humans with multiple sclerosis, which show an increased number of CRF-expressing neurons in the PVN [33].…”
Section: Discussionmentioning
confidence: 83%
“…Considering that two phenotypic CRF neurons occur in the PVN (one non-AVP-producing and the other AVP-coproducing) [32] and that the signal-driving ACTH secretion depends on the nature, intensity, and duration of the stressor [2], it is tempting to speculate that, in contrast to AA in EAE, the non-AVP-producing neuron is the predominant driving neuron, at least in the later stages of the disease (after 11 days). This notion is reinforced by results in humans with multiple sclerosis, which show an increased number of CRF-expressing neurons in the PVN [33].…”
Section: Discussionmentioning
confidence: 83%
“…Increased HPA axis activity has been reported in patients with MS under basal conditions and in response to challenge tests (Michelson et al 1994;Reder et al 1994;Grasser et al 1996;Wei & Lightman, 1997;Fassbender et al 1998;Then Bergh et al 2001). Post-mortem analysis of brains from MS patients has revealed an increase in the number of CRF-positive, AVP-positive neurons in the PVN with no change in the CRF-positive, AVP-negative population (Erkut et al 1995;Purba et al 1995). These data suggest an increased role for AVP in MS. Further support for an increased role for AVP is provided by the observation that MS patients have an increased HPA axis response to AVP compared with controls (Michelson et al 1994).…”
mentioning
confidence: 85%
“…amic CRH neurons as indicated by increased numbers of CRH expressing neurons and an increase in the fraction of these neurons that co-express AVP (Erkut, Hofman, Ravid, & Swaab, 1995;Purba, Raadsheer, Hofman, Ravid, Polman, Kamphorst, & Swaab, 1995;Swaab, 1997). Detailed cHnical studies revealed subtle HPA dysregulations e.g.…”
Section: Immune Activation Induced Hpa Changes and Depressionmentioning
confidence: 99%